Integrated modelling of variable renewable energy-based power supply in Europe. (15th March 2017) - Gils, Hans Christian; Scholz, Yvonne; Pregger, Thomas; Luca de Tena, Diego; Heide, Dominik
Abstract: Variable renewable energy (VRE) resources increasingly add fluctuations to power systems. The required types and capacities of balancing measures, amounts of curtailment, and costs associated with system integration need to be assessed for advising policy makers and economic actors. Previous studies mostly exclude storage from model-endogenous capacity expansion and omit concentrated solar power (CSP) completely. In this study, we stress the need for grid and backup capacity by investigating an integrated market in Europe, allowing for additional short-term as well as long-term storage and considering CSP as a dispatchable backup option. The Renewable Energy Mix (REMix) energy system model is introduced and applied to assess the capacity expansion and hourly dispatch at various levels of photovoltaic and wind power penetration. The model results demonstrate combinations of spatial and temporal balancing measures that enable net photovoltaic and wind supply shares of 60% and 70% of the annual demand, respectively. The usage of storage and grid can keep curtailments below 20% of the demand for theoretical VRE shares of up to 100%. Furthermore, we determine that the VRE supply structure has a strong impact on the least-cost allocation of power plants across Europe but only a limited effect on supply costs. Highlights: We introduce the REMix high temporal and spatial resolution energy system model. We perform a case study on European power supply at various VRE penetration levels. Our results quantify the need for grid, storage, and dispatchable generation. We note that curtailments stay below 20% at VRE supply shares of up to 100%. Supply costs are lower in wind-dominated scenarios than photovoltaic-dominated ones.